EVOLUTION OF RELIGIOUS CAPACITY IN THE GENUS HOMO: TRAIT COMPLEXITY IN ACTION THROUGH COMPASSION: with Margaret Boone Rappaport and Christopher Corbally, "Evolution of Religious Capacity in the Genus Homo: Origins and Building Blocks"; Margaret Boone Rappaport and Christopher Corbally, "Evolution of Religious Capacity in the Genus Homo: Cognitive Time Sequence"; and Margaret Boone Rappaport and Christopher Corbally, "Evolution of Religious Capacity in the Genus Homo: Trait Complexity in Action through Compassion.". Issue 1 (12th February 2018) - Rappaport, Margaret Boone; Corbally, Christopher
Abstract: In this third and last article on the evolution of religious capacity, the authors focus on compassion, one of religious expression's common companions. They explore the various meanings of compassion, using Biblical and early related documents, and derive general cognitive components before an evolutionary analysis of compassion using their model. Then, in taking on neural reuse theory, they adapt a model from linguistics theory to understand how neural reuse could have operated to fix religious capacity in the human genome. They present a teaching tool on "Religious Capacity in Action, " and develop an example of compassionate decision making in very early Homo sapiens in North Africa. They round out their analysis of compassion by exploring theory in neuroscience on a standard decision‐making model, and investigate what goes on in the human brain when a values‐based decision is made.